Autorregulación y programas de cumplimiento empresarial en materia de publicidad comercial y protección al consumidor - Pazos Hayashida, Javier Mihail (2020)
The purpose of this paper is to provide an approach to self-regulation in commercial matters and, specifically, to the self-regulation systems on advertising and consumer protection in Peru. Particularly, the article analyzes the recent adoption of the Supreme Decree N° 185-2019-PCM, Regulation that promotes and regulates the voluntary implementation of regulatory compliance programs on consumer protection and advertising. In this sense, the objectives compliance programs seek to achieve are highlighted and the guidelines to be followed are addressed so that their implementation within a corporation is truly effective, particularly in terms of advertising and consumer protection. Finally, advantages and disadvantages of self-regulation systems are developed and it is concluded that the adoption of compliance programs is positive for consumers, the private sector and authorities.